HPLC METHOD DEVELOPMENT AND VALIDATION FOR QUANTITATION OF TRIGONELLINE FROM MIRABILIS JALAPA LINN. LEAVES AND ENHANCEMENT IN EXTRACTION YIELD FROM ULTRA FINE POWDER - Sathe, Padma S.; Dighe, Vidya V. (International Journal of Current Pharmaceutical Research, 2016)
Objective: Development and validation of a simple and reliable HPLC method for determination of an alkaloid, trigonelline, in the methanolic extract of Mirabilis jalapa Linn. leaves and comparing the extraction yields of trigonelline from micro powder and ultrafine powder. Methods: The quantitation of trigonelline was carried out on a Phenomenex (Luna 5 U RP C8 (2) column, 25 cm x 4.6 mm, i.d. 5 Âµm), using mobile phase comprising of distilled water containing HCl (pH adjusted to 3.5) and methanol in the volume ratio of 70:30, which was delivered at the flow rate of 0.5 ml per min, at 35 Â°C column temperature. The detection and quantitation of trigonelline were carried out using PDA detector at the wavelength Î»=264 nm. Ultra-fine powder of Mirabilis jalapa Linn. was prepared using simple stepwise powdering method. The dried leaves of Mirabilis jalapa Linn. were ground using ice jacketed domestic mixer. This powder was sieved through a BSS 85 mesh sieve and considered as a micro powder. Further fine grinding was done by jet milling, followed by ball milling. This powder was considered as an ultra-fine powder. Results: The proposed HPLC method for quantitation of trigonelline from dried leaf powder of Mirabilis jalapa Linn. is rapid, simple, accurate and precise. Conclusion: The amount of trigonelline obtained using methanolic extracts of Mirabilis jalapa Linn. Ultra-fine powder and the micro powder was found to be 1.1103 mg/g and 0.7258 mg/g respectively.